Bernard Suits’in oyun ve spor anlayışı üstüne (spor felsefesine dair bir çalışma)* - Filiz, Nezih; Erdemli, Atilla; Yorulmazlar, Mehmet Mustafa (My University, 2017)
Suits describes game playing as “voluntarily attempt to overcome unnecessary obstacles”. In this context, he states that human beings create artificial obstacles -to be overcome- and follow the rules, which limit the permissible means to overcome the obstacles and so specify the obstacles, -just because they make the activity possible-. He clarifies the concepts of play, game and sport with reference to his definition of game playing. Likewise, he asserts that there are two reasons to engage in an activity: autotelic or instrumental. The first one expresses that the activity is undertaken as an end in itself and the second one expresses the activity is undertaken as a means to something else. This understanding reminds us the dichotomy which has been discussed in the History of Philosophy ever since the Ancient Times: is an activity done for pleasure (hedone) or happiness (eudomania)? According to the British and American way of life which is grounded in the Utilitarianism of Mill and Bentham, human beings generally seek pleasure and avoid pain. The Utopian world arising from this understanding, becomes a place in which human beings do not need anything. With this, Suits presents autotelic game playing as the ideal of existence for Utopia. On the other hand, the game becomes a Utopian life; when it is played for itself and the athletes play by becoming integrated with the game and with relish. It becomes a Utopian life, when the athletes engage in an activity that is beyond work, family, social relations, artistic tendencies or real daily life, in a word and at the same time when there is no other reason such as winning a prize or an honorary award etc. other than the activity itself.
On Bernard Suits’ understanding of play, sport and games (a study in the philosophy of sport)
Keywords: Spor Felsefesi, oyun, spor, ototelik etkinlik, araçsal etkinlik